The Impact of Investment in Human Capital on the Exports of Goods and Services - Samina Siddique; Zafar Mahmood; Shabana Noureen (NUST Journal of Social Sciences and Humanities, 2021)
With the growth of services economy worldwide, it has become essential for policymakers to comprehend the export competitiveness of nations to identify offshore export locations or alternatively offer their own sites as an exporting location. Human capital investment is considered as a key component in attracting foreign countries for outsourcing purposes. Earlier studies have shown mixed role of human capital investment on off shoring activities. This study assesses the effects of control variables (business environment, wages and IT infrastructure) and human capital investment on export of goods and services from the selected Asian outsourcing countries. Panel Estimated Generalized Least Square (EGLS) technique is used with country weights to specifically overcome the problem of autocorrelation. Empirical findings show that investment in human capital is significant for both goods and services exports. We found a large impact of human capital investment on exports of goods and services in selected Asian countries as compared to selected developed countries. Empirical findings further suggest that human capital is more essential for export of goods than export of services. From these findings, the study draws important implications for policymaking in countries who intend to offer themselves as an attractive location for exporting and for those who intend to locate their production activities overseas.